Analysis of The Influence of Auditor Characteristics and Capital Intensity on Tax Avoidance in Coal Sector Mining Companies - Ayu, Asyfa Gita; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to examine the influence of auditor characteristics proxied by tenure audits and audit opinions, as well as capital intensity on tax avoidance in coal sector mining companies listed on the IDX for the period 2020 – 2023 as the object of the research. Sampling was done using the purposive sampling technique, which was obtained by 10 companies so that the number of samples used was 40 observation data. The data analysis used in this study is by using SPSS 26. The results of this study show that the variables of audit tenure, audit opinion, and capital intensity have no effect on tax avoidance.